Multinational corporations and organization theory post millennium perspectives - Dörrenbächer, Christoph 1961-; Geppert, Mike 1964-
Prelims -- part I: Setting the scene -- part II: Further development of established debates -- part III: New conceptual and methodological approaches in the study of the MNC -- part IV: The contemporary MNC: an internally and externally politicized organization
The study of multinational companies (MNCs) has been split for many decades into two camps which hardly talked to each other: a) predominantly economic and functionalist oriented International Business Researchers, and b) largely social constructivist and critical management oriented Organization Theorists. This volume intends to build bridges by bringing together leading international scholars from both camps, who provide new insights in the study of MNCs. In addition to the bridge-building exercise, the book aims to develop a more comprehensive organizational theoretical understanding as well as methodological plurality in the study of how MNCs function in the post-millennium era, both internally and externally, and also how they control their international operations across economic, institutional, cultural, linguistic, political and social divides. Key topics addressed in our volume include: historical perspectives on the study of MNCs, the role of increased financialization and marketization on MNCs, the new role of the HQ within contemporary MNC, the role of language in MNCs, discursive studies of MNCs, labour representation in MNCs as well as social movements and corporate social responsibility and MNCs
Includes bibliographical references
Keywords: bisacsh; Business & Economics / Organizational Behavior; Organizational theory & behaviour; International business enterprises / Research / Vertical integration; International business enterprises / Social aspects; Betriebswirtschaftslehre; Aufsatzsammlung